Peran pemimpin transformasional membudayakan kerja etis guna meningkatkan organizational citizenship behaviour - Santi Retno Sari; Dita Nurul Aini Mustika Dewi; Kumba Digdowiseiso (Universitas Kristen Maranatha, 2022)
This study aimed to examine the parallel mediation of ethical work climate dimensions on the relationship between transformational leadership and employee organizational citizenship behavior (OCB). This study contributed to the support of transformational leadership literature by proposing a parallel mediation model of ethical work climate dimensions on the relationship between transformational leadership and OCB. This research is associative research, therefore the method used in this research is a quantitative method. This study took a population of employees in two companies in Jakarta. The sample size is based on the Yamane formula calculation and obtained 201 employees as the sample. The sampling technique chosen was the simple random sampling probability sampling method. The analytical technique for testing parallel mediation was using a macro process assisted by SPSS 26 and Process V3.5 tools. The results showed that transformational leadership has a positive and significant impact on employee OCB. The results of the mediation test were supported by data, namely the overall ethical work climate mediates the relationship between transformational leadership and OCB. And on a per-dimensional basis, only the review dimension did not mediate the effect of transformational leadership on OCB. These results revealed that employees will further improve their civic behavior if they are supported by the cultivation of an ethical work climate, especially those that display three dimensions, namely togetherness, equality, and openness. In addition, employees will increasingly display self-sacrificing civic behavior by increasing the application of leadership styles that display a transformational style. Practical implications and suggestions are presented in this study.